AIAA Guidance, Navigation, and Control Conference 2011
DOI: 10.2514/6.2011-6247
|View full text |Cite
|
Sign up to set email alerts
|

Flight Control for a Class of 155 mm Spin-stabilized Projectiles with Course Correction Fuse (CCF)

Abstract: This paper presents a study on trajectory correction autopilot configuration for a class of fin-guided spin-stabilized ammunitions. The proposed algorithm is heavily based on the system's linear parameter-varying model valid inside its entire flight envelope. This model offers an accurate approximation of the airframe nonlinear dynamics and is also used for stability analysis. A decentralized optimal linear quadratic integral servo controller strategy is proposed for the autopilot that offers accurate tracking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…For the Jacobian on the right we can apply the drag-only approximation in sec. II.E.1 and use (14). If we do this and use similar arguments about insensitivity to position and velocity as those leading to (49) we arrive at the approximation…”
Section: Iiib2 Velocity To Be Gainedmentioning
confidence: 92%
See 1 more Smart Citation
“…For the Jacobian on the right we can apply the drag-only approximation in sec. II.E.1 and use (14). If we do this and use similar arguments about insensitivity to position and velocity as those leading to (49) we arrive at the approximation…”
Section: Iiib2 Velocity To Be Gainedmentioning
confidence: 92%
“…The stability and disturbance rejection for 2D canard controlled spinning projectiles can be improved by incorporation of a dynamics synthesizing autopilot and several such designs have been presented recently. 14,15,16 It has been shown that good tracking performance can be achieved e.g. by a controller of the proportional-integral type designed using linear parameter varying theory incorporating ℋ 2 or ℋ ∞ conditions.…”
Section: Ib1 Related Workmentioning
confidence: 99%
“…He pointed out that the stability for this kind of projectiles is reduced due to the following two factors: the addition of canards and the reduced angular momentum of the forward part. Theodoulis and Wernert [14] present the quasilinear parameter-varying model of the dual-spin-stabilized projectile and analysed the stability of the projectile on different characteristic points of the whole flight envelope. Zhu [15] took account of the control effects of canards and then established a revised stability criterion according to the Hurwitz stability criterion which can be reduced to that of conventional spinstabilized projectiles.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate and enhance the performance of dual-spin atmospheric projectiles, several works have been done [1][2][3][4][5][6][7][8][9][10]. In these works, several issues such as dynamic, stability, control, and guidance have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Theodoulis et al [8][9][10] have studied some guidance, control, and dynamic issues in a class of n guided spin stabilized vehicles. In these works, the nose roll angle is controlled by a coaxial servomotor, whereas the lateral guidance and control are performed by two pairs of rotating canards placed on the nose [9,10]. The complete nonlinear equations of motion are stated in a non-rolling body frame [8][9][10].…”
Section: Introductionmentioning
confidence: 99%